Meningkatkan Kemampuan Membaca Huruf Hijaiyah Braille dengan Metode Iqra’ pada Anak Tunanetra - Isma, Muzi Latunil; Taufan, Johandri (Jurnal Penelitian Pendidikan Khusus, 2022)
This research is motivated by the problem that the researchers found in SLB N 1 Padang Panjang, a student who is totally blind who has not been able to mention all the braille hiajiyah letters. The purpose of the study was to improve the ability to read hijaiyah braille using the iqra' method. The type of research used was quantitative with an experimental approach in the form of Single Subject Research (SSR) A-B-A design. Data were analyzed by graphical visual analysis. Techniques in collecting data in the form of tests and data collection tools for test questions. The subjects of this study were children with total blindness in class VII SLB N 1 Padang Panjang. The results of the baseline study (A1) were carried out four times and obtained a stable percentage of 24%, in the intervention condition (B) nine observations were made to obtain a stable percentage of 81%, in the baseline condition (A2) six observations were made by students. obtained a stable percentage of 86%. Based on the results of the study, it can be concluded that the iqra' method can improve the ability to read hiajiyah braille letters in blind children.